2003
DOI: 10.1103/physrevd.68.043506
|View full text |Cite
|
Sign up to set email alerts
|

Lower bound on the neutralino mass from new data on CMB and implications for relic neutralinos

Abstract: In the frame of an effective MSSM model without gaugino-mass unification at a grand unification scale, we set a lower bound on the neutralino mass based on the new WMAP data on ΩCDM (R-parity conservation is assumed). Our lower bound, mχ > ∼ 6 GeV, leaves much room for relic neutralinos significantly lighter than those commonly considered (mχ > ∼ 50 GeV). We prove that these light neutralinos may produce measurable effects in WIMP direct detection experiments of low energy threshold and large exposure.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
127
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 44 publications
2
127
0
Order By: Relevance
“…In Refs. [1,2] we also showed that direct detection rates for light relic neutralinos make these particles detectable with WIMP direct search experiments with current technologies. A comparison of our predictions with intervening experimental results was presented in Ref.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…In Refs. [1,2] we also showed that direct detection rates for light relic neutralinos make these particles detectable with WIMP direct search experiments with current technologies. A comparison of our predictions with intervening experimental results was presented in Ref.…”
Section: Introductionmentioning
confidence: 97%
“…The relic abundance Ω χ h 2 of neutralinos lighter than 50 GeV which arise in our class of gaugino non-universal models has a relatively simple structure in terms of dominant diagrams in the annihilation cross section [1,2]. Here we just remind that combining our calculation of the relic abundance of light neutralinos with the value of (Ω CDM h 2 ) max , an absolute lower bound on the neutralino mass of 6 GeV can be set [1,2].…”
Section: Supersymmetric Models Without Gaugino-mass Unificationmentioning
confidence: 99%
See 3 more Smart Citations